Experimental and numerical investigation of ratcheting and low-cycle fatigue in metal components - Chatziioannou, Konstantinos (The University of Edinburgh, 2020)
Structures loaded cyclically beyond their elastic limit experience gradual accumulation of plastic deformations or strains which may eventually lead to material deterioration and ductile fracture. Assessing the life expectancy of their structural members requires the development and implementation of appropriate material models into the finite element environment, using robust numerical integration schemes. It is the purpose of the present Thesis to investigate through rigorous numerical analyses and experimental testing the mechanical behaviour of metal components subjected to intense cyclic loading. Advanced numerical tools are developed to simulate multi-axial material ratcheting and cyclic plasticity-damage response in metal structural components. The ultra low-cycle fatigue of high-strength steel welded tubular joints is also investigated through large-scale experiments. An implicit numerical scheme is proposed in Chapter 2 for simulating the mechanical response of thin-walled structures subjected to inelastic cyclic loading. The constitutive model is formulated explicitly for plane stress conditions, accounts for combined kinematic/isotropic hardening and follows the von-Mises yield criterion. Emphasis is given to kinematic hardening part, which is described with an advanced multiple backstress model suitable for multi-axial material ratcheting simulation. Constitutive relations are integrated implicitly using the Euler-backward integration technique. Two main novelties of the algorithm refer to the incremental update of the internal variables through the solution of a single scalar equation, and the explicit formulation of the consistent tangent moduli. The numerical scheme is implemented into the finite element software ABAQUS (2016) as a material user-subroutine UMAT and its capabilities are demonstrated through the numerical simulation of large-scale experiments on pipe elbows, a characteristic mechanical component that experiences multi-axial ratcheting response. In the sequence, the proposed ...